PEMBUATAN HERBARIUM DAN SABUN CUCI TANGAN DI SMP NEGERI 24 MALANG - Agatha, Arda Putri Junia; Aini , Rifda Aulia Fajar; Sabrina, Sabrina; Hamimi , Erti; Setyaningrum , Lina; Mulyati , Yayuk; Sugiyanto, Sugiyanto (Inspirasi: Jurnal Pengabdian Masyarakat, 2025)
Making Herbarium and hand soap from butterfly pea flower and lemon extract is a community service activity carried out to provide practical experience to students by connecting natural science with everyday life and introducing plants in the surrounding environment. The community service activity was carried out at SMP Negeri 24 Malang for three days. The method used was practical training with direct assistance and interaction between students. The results of this community service activity showed a positive response and increased skills with students who had succeeded in recognizing the types of moss and fern plants, understanding the important role of moss and fern plants in maintaining the balance of nature, creating learning media, and utilizing natural resources in the school environment as environmentally friendly products. Thus, the activity of making herbarium and hand soap from butterfly pea flower and lemon extract not only provides knowledge on how to utilize natural resources in the surrounding environment, but students gain knowledge about biodiversity, but students can also develop skills, increase awareness of the importance of nature conservation, and build a sense of responsibility for environmental sustainability and health.